508 Conservative Management of Small Bowel Obstruction: A Local Experience. (4th May 2021) - Gonzalez, M; Aker, M; Manjunath, P; Mishra, A; Ward, N
Abstract: Introduction: Post-operative intra-abdominal adhesions remain the leading cause of small bowel obstruction (SBO) representing one of the main diagnoses warranting emergency laparotomies. The National Audit in Small Bowel Obstruction advocates the use of water-soluble contrast agents (WSCA) as initial management of SBO. We aim to assess the role and outcomes of WSCA and its rate in successfully managing SBO non-operatively. Method: We conducted a 2-year retrospective analysis including all patients admitted with adhesive SBO. Outcomes of patients who received WSCA were compared to those who hadn't. Results: 118 patients were included, 27(23%) of which required immediate surgery while 91(77%) were initially managed conservatively. From the latter group, 53(58.2%) received WSCA whilst 38(41.8%) didn't. Of the group that received WSCA, 36(39.5%) were successfully managed non-operatively, compared to 26(28.5%) that didn't, this however lacked statistical significance. LOS didn't differ between these two groups (5 days vs. 5.5 days, p = 0.805). 32% of the patients required eventual surgical intervention needing longer LOS regardless of receiving WSCA (6.6 days vs. 13.6 days p < 0.001). Conclusions: Adhesive SBO can be managed conservatively in up to two-thirds of patients. WSCA usage has a positive impact but needs further assessment in larger studies.